Novel Mobilizable Genomic Island GEI-D18A Mediates Conjugational Transfer of Antibiotic Resistance Genes in the Multidrug-Resistant Strain Rheinheimera sp. D18 - Fu, Jiafang; Zhong, Chuanqing; Zhang, Peipei; Zong, Gongli; Liu, Meng; Cao, Guangxiang (Frontiers in Microbiology, 2020)
Aquatic environments act as reservoirs of antimicrobial-resistant bacteria and antimicrobial resistance genes, and the dissemination of antibiotic resistance from these environments is of increasing concern. In this study, a multidrug-resistant bacterial strain, identified as Rheinheimera sp. D18, was isolated from the sea water of an industrial maricultural system in the Yellow Sea, China. Whole-genome sequencing of D18 revealed the presence of a novel 25.8 kb antibiotic resistance island, designated GEI-D18A, which carries several antibiotic resistance genes (ARGs), including aadA1, aacA3, tetR, tet(B), catA, dfrA37 and three sul1 genes. Besides, integrase, transposase, resolvase, and recombinase encoding genes were also identified in GEI-D18A. The transferability of GEI-D18A was confirmed by mating experiments between Rheinheimera sp. D18 and Escherichia coli 25DN, and efflux pump inhibitor assays also suggested that tet(B) in GEI-D18A was responsible for tetracycline resistance in both D18 and the transconjugant. This study represents the first characterization of a mobilizable antibiotic resistance island in a species of Rheinheimera and provides evidence that Rheinheimera spp. could be important reservoirs and vehicles for ARGs in the Yellow Sea area.